Comparison of Existing and New Total Knee Arthroplasty Implant Systems From the Same Manufacturer: A Prospective, Multicenter Study. (December 2021) - Hamilton, William G.; Brenkel, Ivan J.; Barnett, Steven L.; Allen, Paul W.; Dwyer, Kimberly A.; Lesko, James P.; Kantor, Stephen R.; Clatworthy, Mark G.
Abstract : Introduction: This study evaluated total knee arthroplasty (TKA) outcomes for an Existing-TKA versus New-TKA from the same manufacturer. Methods: TKA outcomes for 752 with Existing-TKA versus 1129 subjects with New-TKA were followed through 2 years using patient-reported outcome measures (PROMs). Responders were assessed per Outcome Measures in Rheumatology-Osteoarthritis Research Society International criteria. Kaplan-Meier implant survivorship was estimated. Radiographs had an independent radiographic review. Results: Two-year follow-up was 84.6% (636/752) for Existing-TKA and 82.5% (931/1129) for New-TKA. Two-year PROMs mean outcomes for New-TKA versus Existing-TKA at 2 years were: Knee Injury and Osteoarthritis Outcome Score (ADL: 89.0 versus 86.8, P = 0.005; pain: 88.9 versus 87.1, P = 0.019; symptoms: 84.1 versus 82.2, P = 0.017; Sport/Rec: 63.9 versus 58.8, P = 0.001; and QOL: 77.0 versus 73.5, P = 0.003), Patient's Knee Implant Performance (overall: 76.5 versus 73.5, P = 0.003; confidence: 8.4 versus 8.1, P = 0.004; stability: 8.6 versus 8.3, P = 0.006; satisfaction: 8.3 versus 8.1, P = 0.042; and modifying activities: 6.6 versus 6.4, P = 0.334), Oxford Knee Score (41.9 versus 41.1, P = 0.027), and EQ5D-3L (0.88 versus 0.88, P = 0.737). Two-year responder rates using WOMAC were 93.9% versus 90.6% ( P = 0.018) for New-TKA versus Existing-TKA. Independent radiographic review showed that tibial and femoral radiolucencies ≥2 mm were similar ( P ≥ 0.05) or favored New-TKA. Implant survivorship was similar between groups (log-rank P = 0.9994). Discussion: New-TKA versus Existing-TKA demonstrated slightly better PROMs with similar radiographic and implant survivorship outcomes.